PERAN PEMUDA SADAR WISATA DESA KOTO MESJID DALAM PENGELOLAAN EKOWISATA SUNGAI GAGAK KABUPATEN KAMPAR - Lisa Fitriyani Simatupang (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2025)
The use of natural resources to create a tourist destination with the dual goals of protecting the environment and enhancing local communities is known as ecotourism. The purpose of this study is to ascertain the involvement of young people who are aware of tourism (POKDARWIS) in administering the Gagak River ecotourism object. Observation and in-depth interviews with the chief of Pokdarwis Koto Mesjid Village, XIII Koto Kampar District, Kampar Regency, were the research methodology used. The findings indicated that members of the tourism-aware youth group played a significant part in the operation of the Gagak river ecotourism. This is evident in efforts to acquire infrastructure that is the result of their labor, in the provision of accessibility, in marketing initiatives, in the utilization of ecological attractiveness, and in other actions.